Bidirectional Relations Between Parenting and Behavior Problems From Age 8 to 13 in Nine Countries - Lansford, Jennifer E (Archīum Ateneo, 2018)
This study used data from 12 cultural groups in nine countries (China, Colombia, Italy, Jordan, Kenya, Philippines, Sweden, Thailand, and the United States; N = 1,298) to understand the cross‐cultural generalizability of how parental warmth and control are bidirectionally related to externalizing and internalizing behaviors from childhood to early adolescence. Mothers, fathers, and children completed measures when children were ages 8–13. Multiple‐group autoregressive, cross‐lagged structural equation models revealed that child effects rather than parent effects may better characterize how warmth and control are related to child externalizing and internalizing behaviors over time, and that parent effects may be more characteristic of relations between parental warmth and control and child externalizing and internalizing behavior during childhood than early adolescence.